Valley of Kings : TombQuest #3 - Northrop, Michael (New York, NY : Scholastic Inc., 2015)
Journeying to the Valley of Kings, Alex and Ren prepare to combat powerful Death Walkers that are causing trouble throughout the world.
Keywords: Mythology, Egyptian -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Egyptian mythology -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Valley of the Kings (Egypt) -- Fiction; Egypt -- Fiction; Valley of the Kings (Egypt) -- Fiction; Egypt -- Fiction; Adventure fiction; Fantasy fiction